Pendampingan Peningkatan Spiritual Masyarakat Desa Payung Melalui Kegiatan Tradisi Barzanji - Risna Syaiful Bahri (Lembaga Riset Ilmiah, 2023)
Marhabanan as a tradition of Muslims and has existed since the time of the Prophet Muhammad. The meaning of the word marhabanan comes from Arabic, namely welcome and has the same meaning as ahlan wasahlan which means welcome, marhabanan is an art as a welcome for something new as was done by the Ansor people (residents of the city of Medina) in welcoming the Prophet and his people. The emigrants arrived in the city of Medina on the occasion of the Prophet Muhammad and his companions moving from the city of Mecca to the city of Medina. In marhabanan, activities about reading the books of al-Barzanji and addiba'i which contain praises to the Prophet Muhammad SAW and the history of birth were sent to be prophets and apostles and until he died. With the hope of getting intercession or help from the Prophet Muhammad later in Yaumul Qiyamah later. Therefore, the Fatayat mothers held marhabanan activities in the hope of getting intercession from him and strengthening the relationship between mothers in Payung village and also increasing piety to Allah SWT. In collecting data sources using qualitative methods, namely by observation, and documentation. Based on the results obtained that there is an increase in the spirituality of the people of Payung Village, especially the Fatayat women of Payung Village.